A new method of seismic retrofitting cost analysis and effectiveness for reinforced concrete structures. (1st November 2021) - Markou, George
Highlights: Cyclic nonlinear analyses are performed through 3D detailed models on full-scale RC structures. In depth analysis of the seismic performance of CFRP sheet retrofitted RC structures. In depth analysis of the seismic performance of infill RC shear wall retrofitted RC structures. A new optimum retrofitting cost effectiveness factor is proposed. A cost effectiveness analysis on the retrofitting strategies is presented. Abstract: Modeling, analysis and design of retrofitting interventions has been a topic of numerous research projects that aim in providing answers to complex questions such as "which retrofitting technique is more effective in terms of cost and frame mechanical enhancement?", and "what is the overall strength enhancement in terms of structural seismic performance?" Therefore, a main purpose of this manuscript is to support decision-making, thus providing a numerical method that can be used to select the optimum retrofit strategy based on the mechanical response of reinforced concrete (RC) structures. The currently available numerical tools for the 3D detailed mechanical limit state study of the structural behavior of retrofitted RC elements are currently bound by numerous numerical and computational constraints, thus are usually implemented at the level of a single structural member under nonlinear or elastic monotonic loading. This work alleviates these constraints through the use of the hybrid modeling (HYMOD) approach [1–3] which is used to develop a finite element model that is numerically validated through the use of a full-scale multistorey RC building that was retrofitted with infill RC walls and carbon fibre reinforced polymer (CFRP) jacketing. Further validation was also performed and presented in this manuscript on joints that foresaw the use of 3 layers of CFRP sheets. The understudy 4-storey RC building, which was experimentally tested under ultimate limit state cyclic loading, was used to develop 24 models that foresaw different retrofitting strategies. Two retrofitting techniques were investigated herein, the CFRP jacketing and the infill RC shear walls, where for the case of the later four different rebar materials were investigated (Steel-, Glass-, Aramid- and Carbon-FRP). In order to determine the optimum cost-effectiveness of each strengthening intervention, an optimum retrofitting cost-effectiveness factor is proposed that takes into account the overall cost of the retrofitting strategy in relation to the respective strength and energy dissipation enhancement that is achieved compared to the initial bare RC frame. Based on the proposed factor and the numerical findings during the seismic assessment of the understudy retrofitting strategies, it was concluded that the use of infill RC shear walls with Aramid-FRP rebars was the most cost-effective strengthening method when both strength and energy dissipation enhancement was within the desired design. For the case where the main objective was the increase of strength (base shear) the use of infill RC shear walls with CFRP rebars was found to be the most cost-effective option. Furthermore, when comparing standard steel-reinforced shear walls with CFRP jacketing, the use of CFRP sheets was found to be more cost-effective in the case where strength enhancement was the main objective. According to the numerical investigation performed herein, more numerical investigation is deemed necessary for the study of the cost-effectiveness of more strengthening methods and seismic isolation systems, where more RC structures and bridges will also be considered.